2008
DOI: 10.1111/j.1472-4669.2008.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial thiosulphate reaction arrays: the interactive roles of Fe(III), O2 and microbial strain on disproportionation and oxidation pathways

Abstract: In this work, we experimentally evaluate pH and SO4(2-) dynamics associated with abiotic and microbial S2O3(2-) oxidation under varying [O2], [Fe(III)] and microbial strain/consortia (two pure strains, Acidithiobacillus ferrooxidans, Acidithiobacillus thiooxidans, their consortia, and two enrichments from an acidic environmental system, Moose Lake 2002 and Moose Lake 2003). Results of the batch experiments demonstrate highly active microbial processing of S2O3(2-) while abiotic controls under identical experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…For example, Thiobacilus ferroxidans yields thiosulfate and tetrathionate; T. tepidarius yields diothionate and T. versutus oxidizes thiosulfate without intermediates and accumulate sulfur (Wentzien et al, 1994). In some cases, the bacteria population will influence the final product of the reaction; however, these final products will also be determined by the conditions of the solution (Warren et al, 2008;Wentzien et al, 1994).…”
Section: Thiosulfate and Microorganismsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Thiobacilus ferroxidans yields thiosulfate and tetrathionate; T. tepidarius yields diothionate and T. versutus oxidizes thiosulfate without intermediates and accumulate sulfur (Wentzien et al, 1994). In some cases, the bacteria population will influence the final product of the reaction; however, these final products will also be determined by the conditions of the solution (Warren et al, 2008;Wentzien et al, 1994).…”
Section: Thiosulfate and Microorganismsmentioning
confidence: 97%
“…Under acidic conditions, thiosalts will be susceptible to disproportionation, meaning that the compounds will oxidize regardless of the microbial activity. Warren et al (2008) identified disproportionation as important for the initial microbial processing of thiosulfate. At basic conditions, the most likely mechanism is that microorganisms change the oxidation state of sulfur oxidizing thiosulfate to tetrathionate and then to sulfate as reported in reaction 7 (Sorokin and Tourova, 2005).…”
Section: Downloaded By [University Of Connecticut] At 17:19 12 Octobementioning
confidence: 98%
“…In the present study it was found that thiosulfate was a short-lived intermediate during tetrathionate oxidation to sulfate. Warren et al (2008) examined thiosulfate oxidation using At. thiooxidans and At.…”
Section: Effects Of Cations On Tetrathionate Oxidationmentioning
confidence: 99%
“…Microbially reversible reduction of Fe (III) to Fe (II; Pentrakova et al, ) also controls S‐disproportionation in clay minerals. At near‐neutral or high pH, Fe 3+ reduction induces S‐disproportionation unlike total oxidation to SO 4 2− and H + at low pH and forms polythionates or elemental S°(Warren et al, ) with precipitation of goethite (FeOOH). Many of these features are evident in the CIB red clay (Nath et al, ; Mascarenhas‐Pereira & Nath, ) and are proxies indicative of S‐disproportionation.…”
Section: Discussionmentioning
confidence: 99%